Assessing Pedestrian Walkability: Improving University Access Via Public Transport in Algiers - ACHOURA, Sarra; HARAOUBIA, Imane; MOHINO SANZ, Maria Inmaculada; BAOUNI, Tahar (Indonesian Journal of Social Science Research, 2024)
This study assesses the walkability of 16 pedestrian routes con-necting public transport stations to the University of Algiers, fo-cusing on safety, comfort, accessibility, connectivity, and pedestri-an traffic flow. The selected routes represent key pathways fre-quently used by students commuting between public transport hubs and the university, chosen due to their high foot traffic and significance for daily student mobility. A mixed-methods approach was employed, combining field observations, interviews with 120 students, and mapping using Google Earth to provide a compre-hensive spatial analysis. To evaluate walkability, a model was de-veloped that includes a scoring system based on five criteria, with each route assessed and categorized as Highly Walkable, Moder-ately Walkable, Slightly Walkable, or Not Walkable. This model en-abled a structured assessment, using tables to quantify aspects like safety (lighting, crossings), comfort (sidewalk quality, shade), and accessibility. Results indicate that while connectivity between transport hubs and the university is consistently high, there are significant disparities in safety, comfort, and accessibility. Route 03 scored well in terms of overall walkability, whereas others like Route 05 and Route 06 were categorized as Not Walkable due to major deficiencies in safety and infrastructure. High congestion during peak hours also emerged as a challenge for many routes. Recommendations for improvement include enhancing safety fea-tures, upgrading comfort amenities, increasing accessibility for individuals with disabilities, and managing pedestrian congestion. These findings aim to inform urban planning efforts to create safer, more comfortable pedestrian infrastructure for university stu-dents in Algiers.